Proteomics of developing pea seeds reveals a complex antioxidant network underlying the response to sulfur deficiency and water stress. (9th February 2021) - Henriet, Charlotte; Balliau, Thierry; Aimé, Delphine; Le Signor, Christine; Kreplak, Jonathan; Zivy, Michel; Gallardo, Karine; Vernoud, Vanessa
Abstract : Proteomics of early developing pea seeds subjected to sulfur and/or water deficiency reveals the presence of a complex antioxidant network and provides insights into stress responses. Abstract: Pea is a legume crop producing protein-rich seeds and is increasingly in demand for human consumption and animal feed. The aim of this study was to explore the proteome of developing pea seeds at three key stages covering embryogenesis, the transition to seed-filling, and the beginning of storage-protein synthesis, and to investigate how the proteome was influenced by S deficiency and water stress, applied either separately or combined. Of the 3184 proteins quantified by shotgun proteomics, 2473 accumulated at particular stages, thus providing insights into the proteome dynamics at these stages. Differential analyses in response to the stresses and inference of a protein network using the whole proteomics dataset identified a cluster of antioxidant proteins (including a glutathione S-transferase, a methionine sulfoxide reductase, and a thioredoxin) possibly involved in maintaining redox homeostasis during early seed development and preventing cellular damage under stress conditions. Integration of the proteomics data with previously obtained transcriptomics data at the transition to seed-filling revealed the transcriptional events associated with the accumulation of the stress-regulated antioxidant proteins. This transcriptional defense response involves genes of sulfate homeostasis and assimilation, thus providing candidates for targeted studies aimed at dissecting the signaling cascade linking S metabolism to antioxidant processes in developing seeds.